CLINICAL SIGNIFICANCE OF B-CELL ACTIVATING FACTOR BAFF IN CHILDREN WITH SYSTEMIC LUPUS ERYTHEMATOSUS - Mirjavadli, R.M. (World of Medicine and Biology, 2025)
The study involved 17 children with systemic lupus erythematosus receiving treatment at the Educational Therapeutic Clinic of Azerbaijan Medical University. The mean age was 15.7±0.5 years. In all patients amount of B-cell activating factor–BAFF, anti nuclear antibodies, anti-double-stranded deoxyribonucleic acid and single-stranded deoxyribonucleic acid antibodies, IgA, IgM, IgG, IgE, circulating immune complexes in serum were determined. The disease activity level was calculated according to the SLEDAI–2k scale. The amount of BAFF increased in SLE patients, and more so in patients with high activity compared with patients with moderate activity (6.6 ng/ml and 4.3 ng/ml, respectively). There is a positive reliable relationship between BAFF and the circulating immune complexes (ρ=0.829; p=0.021), anti-double-stranded deoxyribonucleic acid antibodies (ρ=0.854; p=0.003) and the SLEDAI–2k index (ρ=0.613; p=0.009). The development and improvement of anti-BAFF therapy in children may be considered more appropriate than the conventional therapy used.